A longitudinal study of agriculture households in Indonesia: The effect of land and labor mobility on welfare and poverty dynamics. (December 2020) - Moeis, Faizal Rahmanto; Dartanto, Teguh; Moeis, Jossy Prananta; Ikhsan, Mohamad
Highlight: Agriculture is a vital sector to ensure the livelihood of 32% Indonesia population. Lewis' dual theorem was true in the early 2000s but faded at the end of 2010s. Moving out of agriculture does not guarantee that farmers will become better off. Farmers might not have the skills required to shift in formal sectors. Keeping farmland ownership should be a concern in agriculture development. Abstract: The conventional wisdom of Arthur Lewis's dual sector model says that households in the agricultural (traditional) sector who can move out to a non-agricultural (modern) sector will become better off. We then scrutinize the last three waves of the Indonesia Family Life Survey (IFLS) to analyze the existence of the dual theorem. Our study uses Difference in Difference (DiD) regressions and ordered logit regressions to confirm that moving out of agriculture sectors has significantly increased the welfare of poor agricultural households, especially in the period of 2000–2007, but this is not the case of 2007–2014. Movement out of agricultural sectors decreases the probability of being always poor by 13.5 percentage points. However, when the economy transforms into a more advanced economy, simply moving out of agriculture does not guarantee that farmers, especially landless farmers, will become better off. Welfare improvement requires a shifting to formal non-agricultural sectors, but unfortunately farmers might not be readily equipped with the skills required in formal sectors. Our study also obviously confirms that farmland is an important asset for agricultural households. Agricultural households experiencing a decrease of agricultural land also decreased their expenditure per capita by IDR 36, 833 in 2000 and IDR 68, 683 in 2007. These findings suggest that, currently, moving out of agriculture is not the solution to improve the well-being of farmers. Keeping farmland ownership, raising investment in human capital, and the modernization of agriculture should be the main concerns in agricultural development.